Comparative analysis of long-term outcomes of primary posterior continuous curvilinear capsulorhexis in pseudoexfoliation syndrome - E.V. Egorova; V.V. Chernykh (РМЖ "Клиническая офтальмология")
E.V. Egorova, V.V. Chernykh Novosibirsk Branch of S.N. Fedorov NMRC “MNTK “Eye Microsurgery”, Novosibirsk, Russian Federation Background: primary posterior continuous curvilinear capsulorhexis (PPCCC) is widely used in cataract surgery. However, its safety and efficacy in pseudoexfoliation syndrome (PEX) remain elusive. Aim: to assess long-term outcomes of PPCCC in patients with cataract and PEX. Patients and Methods: 173 patients (213 eyes) aged 50–84 years with PEX were enrolled in the study. All patients were subdivided into two groups. Study group included 78 patients (91 eyes) in who PPCCC was performed. Control group included 95 patients (122 eyes) in who standard phaco without PPCCC was performed. All patients underwent visual acuity measurements, slit lamp examination, and optical coherence tomography (OCT). Postoperative follow-up was 2 to 8 years. Results: the status of the posterior capsule (i.e., folds, fibrosis, sagging, lens epithelial cell proliferation), retrolental space, and anterior hyaloid membrane was assessed by OCT. Optical axis opacification was revealed in 91 eyes (74.6%) of the control group and 1 eye (1.1%) of the study group. Dislocation of capsular bag-intraocular lens was revealed in 5 patients (5 eyes, 4.1%) of the control group. High-level visual acuity remained stable during the follow-up period in the study group while visual acuity in the control group was significantly lower. Conclusion: comparative analysis of long-term surgical outcomes in patients with PEX has demonstrated high efficacy of PPCCC to prevent secondary cataract as well as high significance of the differences in the functional outcomes in the groups during the follow-up period. Keywords: cataract, posterior continuous curvilinear capsulorhexis, pseudoexfoliation syndrome, secondary cataract. For citation: Egorova E.V., Chernykh V.V. Comparative analysis of long-term outcomes of primary posterior continuous curvilinear capsulorhexis in pseudoexfoliation syndrome. Russian Journal of Clinical Ophthalmology. 2019;19(4):195–200.